When Eucharists Attack: Discerning the Body in Cyprian’s On the Lapsed - Anderson, Sonja G. (Harvard theological review, 2025)
Cyprian of Carthage’s On the Lapsed, written in the aftermath of the third-century Decian persecution, contains several stories of the eucharist attacking apostate Christians. These Christians claimed they had been admitted to the eucharist by local, highly esteemed martyrs and confessors. Cyprian, who had fled during the persecution and been unpopular since the day of his election, could not afford to confront this group directly. Instead, he crafted a text that conjured up an autonomous eucharist that policed itself against unworthy intruders. Moreover, he used the graphic language of bodily suffering and dismemberment to scramble the boundaries between lapsed Christian, bishop, and martyr, essentially reconfiguring himself as a martyr.